Cover Feature: Protein Crystallography and Site‐Direct Mutagenesis Analysis of the Poly(ethylene terephthalate) Hydrolase PETase from Ideonella sakaiensis (ChemBioChem 14/2018). (27th June 2018) - Liu, Bing; He, Lihui; Wang, Liping; Li, Tao; Li, Changcheng; Liu, Huayi; Luo, Yunzi; Bao, Rui
Abstract : The cover feature picture shows that PETase, a newly discovered enzyme from Ideonella sakaiensis, has high efficiency and specificity towards PET plastics compared to other similar enzymes (such as cutinase, esterase, or lipase). We have analyzed its crystal structure and improved its catalytic efficiency through site mutagenesis. The results suggest that this enzyme has valuable potential for further study and applications. More information can be found in the communication by Y. Luo, R. Bao, et al. on page 1471 in Issue 14, 2018 (DOI: 10.1002/cbic.201800097 ).